PERAN GURU TERHADAP PEMBENTUKAN KARAKTER DISIPLIN SISWA DI MADRASAH IBTIDAIYAH - Karami, Dzakirina Dzul; Indriyani, Nina; Farisia, Hernik (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2017)
This research aims to determine the role of teachers in shaping students' discipline at MI Al-Karim Surabaya, specifically for all fourth-grade students. This research is descriptive qualitative, with the subjects being fourth-grade teachers and 24 students. The research object is the role of teachers in overcoming students' learning discipline problems. The instruments used were interviews, observation, and documentation. The research findings revealed five forms of student discipline character and four forms of teacher roles in student discipline. The five forms of student discipline character include arriving on time, wearing complete uniforms, bringing textbooks, maintaining classroom cleanliness, and leaving the classroom without permission. Then, the roles of teachers include teachers as educators, teachers as instructors, teachers as mentors, and teachers as trainers. Which, in its various roles, has a very significant impact on the development of discipline in students. This is very evident in the results of the researcher's classroom observations, where students are very obedient to the rules stated in the classroom, as I explained earlier. In addition, this study also identifies several supporting and inhibiting factors in the formation of students' disciplined character. The main supporting factors are good cooperation between teachers, students, and parents, as well as the consistent application of habituation methods, role modeling, and the provision of rewards and punishments. Meanwhile, the most frequently encountered inhibiting factors are the lack of parental supervision at home and the limited time teachers have to monitor all student activities at school. Therefore, synergy between the school and family is essential for the optimal and sustainable development of disciplined character, and the active role of teachers is crucial in shaping students' disciplined character thru consistent example, guidance, and supervision.